Hā Ora: secondary care barriers and enablers to early diagnosis of lung cancer for Māori communities - Kidd J; Cassim S; Rolleston A; Chepulis L; Hokowhitu B; Keenan R; Wong J; Firth M; Middleton K; Aitken D; Lawrenson R (BioMed Central Ltd, 2021)
Background Lung Cancer is the leading cause of cancer deaths in Aotearoa New Zealand. Māori communities in particular have higher incidence and mortality rates from Lung Cancer. Diagnosis of lung cancer at an early stage can allow for curative treatment. This project aimed to document the barriers to early diagnosis and treatment of lung cancer in secondary care for Māori communities. Methods This project used a kaupapa Māori approach. Nine community hui (focus groups) and nine primary healthcare provider hui were carried out in five rural localities in the Midland region. Community hui included cancer patients, whānau (families), and other community members. Healthcare provider hui comprised staff members at the local primary healthcare centre, including General Practitioners and nurses. Hui data were thematically analysed. Results Barriers and enablers to early diagnosis of lung cancer were categorised into two broad themes: Specialist services and treatment, and whānau journey. The barriers and enablers that participants experienced in specialist services and treatment related to access to care, engagement with specialists, communication with specialist services and cultural values and respect, whereas barriers and enablers relating to the whānau journey focused on agency and the impact on whānau. Conclusions The study highlighted the need to improve communication within and across healthcare services, the importance of understanding the cultural needs of patients and whānau and a health system strategy that meets these needs. Findings also demonstrated the resilience of Māori and the active efforts of whānau as carers to foster health literacy in future generations.
Keywords: Barriers; Diagnosis; Hospital; Lung Cancer; Māori; Secondary care; Early Detection of Cancer; Female; Health Literacy; Health Services Accessibility; Health Services, Indigenous; Humans; Lung Neoplasms; Male; Native Hawaiian or Other Pacific Islander; New Zealand; Secondary Care